Transversalidade nos modos de socialização e individuação: experiências juvenis em rede - Juliana Batista dos Reis (2014)
This thesis seeks to describe and understand the socialization and individuation process of a Belo Horizonte urban peripherys young residents, the Algomerado da Serra. The intersection youth/periphery/internet was the investigations starting point, theme that expanded in the investigative route. Therefore, we focus on the interlacement between youth experiences on the internet, within the housing, in the family, at work, among others. The modes of existence of youth are investigated e comprehended in this transversality. Attempting to develop some kind of sociology of individuals, the methodological perspective sought to enhance the understanding of the processes of socialization from the individuals perspective. The research was developed through the ethnography (online and offline), the attendance of youth in their experiences, the realization of individual interviews, privileging the biographical dimension of the subjects. Using authors of sociology of the individual (MARTUCCELLI, ARAUJO, LAHIRE) of sociology of education (DUBET, SETTON) and of sociology of youth (PAIS, DAYRELL), the theoretical-methodological way prioritized to understand the contemporary structural process of from plural experiences of two young people. The internet reveals itself as a dynamic environment, used to express the periphery as an affective territory. The cyberspace is transverse vector in juvenile everyday, a dimension that can be touched upon by many ways, including others places of socialization such as family, school and work. The young constitution as subjects is compromised with a multiplicity of socialization processes, heterogeneous, fluid, in tension. There is intense participation of the youth in these process, which enables their individuation modes and defines them as singulars.